2012
DOI: 10.1371/journal.pone.0050250
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between Active and Observational Learning from Positive and Negative Feedback in Parkinsonism

Abstract: Feedback to both actively performed and observed behaviour allows adaptation of future actions. Positive feedback leads to increased activity of dopamine neurons in the substantia nigra, whereas dopamine neuron activity is decreased following negative feedback. Dopamine level reduction in unmedicated Parkinson’s Disease patients has been shown to lead to a negative learning bias, i.e. enhanced learning from negative feedback. Recent findings suggest that the neural mechanisms of active and observational learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
(68 reference statements)
2
16
0
Order By: Relevance
“…Some studies showed that learning and retention of memory, required for optimal response choice, are significantly reliant on dopamine in Alzheimer's Disease [29,30]. However, some studies found that dopamine impairs or have no effect on, stimulus-response learning and working memory in Parkinsonism or MHE [31,32,33], similarly in our present study we displayed that overproduction of DA is a feature for memory impairment in MHE. Brodskii VY et al reported that dopamine disorganizes the rhythm of protein synthesis in hepatocytes in vitro and in vivo [34,35], indicating the relationship of elevation of DA with liver cirrhosis on the other side.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies showed that learning and retention of memory, required for optimal response choice, are significantly reliant on dopamine in Alzheimer's Disease [29,30]. However, some studies found that dopamine impairs or have no effect on, stimulus-response learning and working memory in Parkinsonism or MHE [31,32,33], similarly in our present study we displayed that overproduction of DA is a feature for memory impairment in MHE. Brodskii VY et al reported that dopamine disorganizes the rhythm of protein synthesis in hepatocytes in vitro and in vivo [34,35], indicating the relationship of elevation of DA with liver cirrhosis on the other side.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, although our findings in the present study must primarily be conceived as purely in vitro model data, they may also have some bearing in understanding liver cirrhosis complicated with MHE, when a disruption of the BBB is prone to occur. Numerous studies describe the specific effects of DA manipulations on learning and how low doses of DA facilitate cognitive abilities [25][26][27]; however, some studies (including our studies) show that overproduction of DA impairs learning and working memory [6][7][8][9]28]. Chronic HE patients exhibit abnormalities in their dopaminergic systems, including an increase in the brain content of DA metabolites [29] and increased turnover of DA [30].…”
Section: Discussionmentioning
confidence: 70%
“…While some studies report performance to be unaltered in the OFF state compared with controls (Cools et al, 2006, Rutledge et al, 2009, Smittenaar et al, 2012, Moustafa et al, 2008, other studies report that reward-based learning is actually impaired relative to punishment (Bodi et al, 2009, Kobza et al, 2012, Frank et al, 2004, Palminteri et al, 2009. The pattern of impaired reward versus punishment learning in PD patients OFF medication resembles that described above in depressed individuals (non-PD) (Clark et al, 2009, Eshel andRoiser, 2010) and concurs generally with suggestions that striatal dopamine depletion contributes to depression in PD.…”
Section: Introductionmentioning
confidence: 55%